A community for students.
Here's the question you clicked on:
 0 viewing
Loujoelou
 3 years ago
If you were to use the elimination method to solve the following system, choose the new system of equations that would result after the variable y is eliminated in the first and second equations, then the second and third equations.
3x – y + 3z = 1
4x + y – 6z = 3
4x – 2y + 3z = –3
7x – 3z = 4
12x – 9z = 3
7x – 3z = 4
4x – 6z = 3
3x + 3z = 1
12x – 9z = 3
3x + 3z = 1
4x – 6z = 3
Loujoelou
 3 years ago
If you were to use the elimination method to solve the following system, choose the new system of equations that would result after the variable y is eliminated in the first and second equations, then the second and third equations. 3x – y + 3z = 1 4x + y – 6z = 3 4x – 2y + 3z = –3 7x – 3z = 4 12x – 9z = 3 7x – 3z = 4 4x – 6z = 3 3x + 3z = 1 12x – 9z = 3 3x + 3z = 1 4x – 6z = 3

This Question is Closed

ParthKohli
 3 years ago
Best ResponseYou've already chosen the best response.1I prefer a question at a time. I'd help you with the first.

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1Lol it is a question, 9ut the last 8 sets are choices.

ParthKohli
 3 years ago
Best ResponseYou've already chosen the best response.1Start by adding the top two equations.

waterineyes
 3 years ago
Best ResponseYou've already chosen the best response.0What do you get?? @Loujoelou

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1I know it's either C/D, cause 3x+3z=1 is what you get when you eliminate y from 1st/2nd equation.

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1nvm other way around. It's A/B

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1Cause you get 7x3z=4 not what I said earlier.

ParthKohli
 3 years ago
Best ResponseYou've already chosen the best response.1Now, you multiply the second equation by 2 and then add equation 1 and 2.

waterineyes
 3 years ago
Best ResponseYou've already chosen the best response.0Now multiply second equation by 2 and then add second and third equation and let us see what you get.

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1K I get it now :) It's A cause you get 12x9z=3. Was just a little confused about it.

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1tyvm @waterineyes @ParthKohli I understand it perfectly now :) At least doing this by elimination method I mean.

ParthKohli
 3 years ago
Best ResponseYou've already chosen the best response.1You got the thing successfully. Congratulations, Lou!

waterineyes
 3 years ago
Best ResponseYou've already chosen the best response.0You are doing this by elimination only @Loujoelou

Loujoelou
 3 years ago
Best ResponseYou've already chosen the best response.1Lol thx @ParthKohli and yes for this problem I had to @waterineyes
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.